Analisis Derajat Desentralisasi Fiskal di Provinsi Sulawesi Tenggara Tahun 2016-2020 - Wa Ode Sarlina; Ishak; Liman (Yayasan Literasi Sains Indonesia, 2022)
One form of the implementation of regional autonomy is the existence of autonomy in the aspect of regional financial management which is called fiscal autonomy. Fiscal autonomy is the delegation of responsibilities and the distribution of power and authority for decision-making in the fiscal sector, which includes both revenue and expenditure aspects. Fiscal decentralization is linked to the duties and functions of local goverment in providing public goods and services. This study aims to analyze the degree of fiscal decentralization in Southeast Sulawesi Province in 2016-2020.The degree of fiscal decentralization is a measure of the ability of local goverment in order to increase Local Own Revenue which is used to finance development in Southeast Sulawesi Province. This is study uses secondary data. The analytical tool used in this study is quantitative analysis, namely the analysis of the degree of fiscal decentralization, namely the ratio between Regional Original Income and Total Revenue Regional. The results showed that the degree of fiscal decentralization of Southeast Sulawesi Province in 2016-2020 fluctuated with an average 0f 25,25% so it could be said that it was still in the moderate category.